Adhesion, Biofilm Formation, and luxS Sequencing of Campylobacter jejuni Isolated From Water in the Czech Republic - Shagieva, Ekaterina; Teren, Martin; Michova, Hana; Strakova, Nicol; Karpiskova, Renata; Demnerova, Katerina (Frontiers in Cellular and Infection Microbiology, 2020)
The microaerophilic pathogen Campylobacter jejuni is a leading bacterial cause of human gastroenteritis in developed countries. Even though it has a reputation as a fastidious organism, C. jejuni is widespread and can be easily isolated from various animals, food, and environmental sources. It is suggested that an ability to form biofilms is probably necessary for the survival of C. jejuni under harsh environmental conditions. The first step required for successful biofilm formation is adhesion to a suitable surface. Therefore, in this work, the degree of adhesion was evaluated, followed by characterization and quantification of biofilms using confocal laser scanning microscopy (CLSM). A total of 15 isolates of C. jejuni were used in the experiments (12 isolates from surface and waste waters, 1 human clinical, 1 food and 1 ACTT BAA 2151 collection strain, all samples originated from the Czech Republic). Regardless of the sample origin, all C. jejuni isolates were able to adhere to the polystyrene surface within 30 minutes, with the number of attached cells increasing with the time of incubation. The resulting data showed that all isolates were able to form complex voluminous biofilms after 24 hours of cultivation. The average amount of biovolume ranged from 3.59 x 106 µm3 to 17.50 x 106 µm3 in isolates obtained from different sources of water, 16.79 x 106 µm3 in the food isolate and 10.92 x 106 µm3 in the collection strain. However, the highest amount of biomass was produced by the human clinical isolate (25.48 x 106 µm3). Similar to the quantity, the architecture of the biofilms also differed, from a rugged flat monolayer of cells to large clustered structures. Further, all isolates were tested for the presence of the luxS gene, as the luxS/AI-2 (autoinducer-2) quorum sensing pathway has been previously connected with enhanced biofilm formation. Two isolates originated from surface waters did not possess the luxS gene. These isolates formed thinner and sparser biofilms lacking the presence of significant clusters. However, the ability to adhere to the surface was preserved. The sequencing of the luxS-containing fragments shown a high similarity of the luxS gene among the isolates.